FORMING ANALYSIS OF METAL-COMPOSITE SANDWICH STRUCTURES - Sivakumar, Dhar Malingam (2010)
This study investigates the effect of preheat temperature, blank holder force and feed rate on the formability of metal-composite sandwich structures. Blank holder force was found to be the dominant factor governing the formability of this class of material. Higher forming temperatures have an adverse effect on the forming quality while feed rates do not have significant effect. The finite element model developed to model this structure gives a good strain evolution correlation with the experimental results. This unified approach of combining analytical, computational and experimental methodologies provided a fundamental understanding of the formability behaviour of metal-composite sandwich structures.